Open access musicology : Volume one - Epstein, Louis K.; Barolsky, Daniel (2020)
Cracking the musical code: what notation can tell us about our musical values / S. Andrew Granade – Ancient Mesopotamian music, the politics of reconstruction, and extreme early music / Samuel Dorf – An intermedia approach to seventeenth-century English popular song culture / Sarah F. Williams – Instrumental music in early seventeenth-century Italy: instruments as vehicles of discovery / Rebecca Cypess – MacDowell's vanishing Indians / Dan Blim – Jenny Lind and the making of mainstream American popular music / Julia Chybowski – Listening to music history / Nathan C. Bakkum.